(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The Government of India has imposed an unprecedented 21-day national lockdown, as part of a series of steps to reduce the transmission of the Covid-19, on 25.03.2020. The virus had assumed the status of a pandemic, impacting almost every country across the globe including India. The measures taken by the government of India and various other state governments poses serious legal challenges.